Food Socio-Politics And Sharia Finance In Indonesia: Agricultural Development In Islamic Political Economic Perspectives - Mustapa, Hasan; Saripudin, Udin (Univeristas Islam Bandung, 2022)
This paper seeks to examine the value of the government's role in enhancing investment from Islamic funding in the agricultural sector. This sector needs to be reinforced to serve as the basis for national food security. Agricultural landscape 's abundant potential will hopefully fulfill national needs and become a pillar of exports. This effort was hampered by the high risk that the capital aspects of the agricultural sector were faltering without certainty of profit making. With descriptive analysis the methodology used is qualitative. The result showed The economic prospects of Islamic agricultural policy were strong, but the lack of effective support for infrastructure gave rise to many weaknesses in socio-economic growth, socio-economic development, despite efforts to establish a sustainable society, public interests and reliable agricultural resources. It is worth considering the possible financing of the Hajj Financial Management Agency (HFMA) for the agricultural sector. The government must tighten regulations to foster a healthy partnership ecosystem between the Ministry of Agriculture, Islamic Financial Institutions, and high-quality agricultural resources.